Tinjauan Transaksi Produk di Bank Sampah Sejahtera Kemiling Perspektif Ekonomi Islam - Reka, Novia; Albab, Ulil; Mawardi, .; Abizar, .; Harahap, Sofyan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
A problem that occurs in each individual or group cannot be separated from an ecological point of view, because climate has an important point of view in everyday life. One of the natural problems that until now has not been resolved is the waste problem, because most of the waste is something that is easily thrown away or not used at all. There must be cooperation from all parties in overcoming the waste problem, so that the limit for the final disposal site (TPA) can be reduced. The presence of Garbage Banks conducted in several areas of Bandar Lampung is expected to be able to take a positive value from waste. The problem plan in this exploration is: First, what items are used in the Waste Bank. Second, what is the perspective of the aspect of Islamic Finance on the exchange of goods utilized at the Garbage Bank. This examination is a field research using a subjective strategy. This study is nothing but someone's words, whether composed or spoken by someone, perceptions, meetings and documentation which are focused on gathering information at the waste bank in Bandar Lampung. The subjects of this research were pioneers in the local area, several supervisors of the Garbage Bank and several residents and customers of the Garbage Bank. The impact of the exchange exploration used in the Garbage Bank and the impact of the existing reality are: The exchange used in the Garbage Bank uses supporting goods in the form of waste reserve funds and garbage containers, as well as assets carrier goods in accordance with existing exchanges. In Islamic Economics, exchanges made at wasteful banks do not contain components that prohibit monetary exchanges such as usury, gharar, maysir, and others Keywords: Transactions, Garbage Banks, Riba, Islamic Economics